ABS modified with hydrogenated polystyrene‐grafted‐natural rubber. Issue 1 (3rd November 2012) - Pisuttisap, Anawat; Hinchiranan, Napida; Rempel, Garry L.; Prasassarakich, Pattarapan
Abstract Natural rubber (NR) latex was grafted by emulsion polymerization with styrene monomer, using cumene hydroperoxide/tetraethylene pentamene as redox initiator system. The polystyrene‐grafted NR (PS‐g‐NR) was hydrogenated by diimide reduction in the latex form using hydrazine and hydrogen peroxide with boric acid as a promoter. At the optimum condition for graft copolymerization, a grafting efficiency of 81.5% was obtained. In addition, the highest hydrogenation level of 47.2% was achieved using a hydrazine:hydrogen peroxide molar ratio of 1:1.1. Hydrogenation of the PS‐g‐NR (H(PS‐g‐NR)) increased the thermal stability. Transmission electron microscopy analysis of the H(PS‐g‐NR) particles revealed a nonhydrogenated rubber core and hydrogenated outer rubber layer, in accordance with the layer model. The addition of H(PS‐g‐NR) at 10 wt % as modifier in an acrylonitrile–butadiene–styrene (ABS) copolymer increased the tensile and impact strengths and the thermal resistance of the ABS blends, and to a greater extent than that provided by blending with NR or PS‐g‐NR. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013